2006
DOI: 10.1063/1.2162810
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and magnetostriction behaviors during the nanocrystallization of the amorphous Ni5Fe68.5Si13.5B9Nb3Cu1 alloy

Abstract: The changes in the magnetic properties ͑coercive field and saturation magnetostriction͒ of Ni 5 Fe 68.5 Cu 1 Nb 3 Si 13.5 B 9 amorphous alloy after thermal treatment are reported. In order to develop a nanocrystalline structure, the thermal annealing was carried out by Joule heating currents of 1.7 and 1.8 A during different annealing times. Additionally, a microstructural characterization of the treated samples was performed by x-ray diffraction, determining the partial volume of the two, crystalline grains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The amorphous character of the as-cast ribbons was confirmed by both, XRD and Transmission Electron Microscopy analysis. It was found that thermally treated ribbons show the formation of bcc-(Fe, Co[Si]) and fccCo phases for COF samples and bcc-(Fe, Ni[Si]) for NIF ones [7]. The thermal treatments on the as-cast ribbons were carried out in air by Joule-heating during short time (always below 5 min).…”
Section: Sample Treatmentsmentioning
confidence: 99%
“…The amorphous character of the as-cast ribbons was confirmed by both, XRD and Transmission Electron Microscopy analysis. It was found that thermally treated ribbons show the formation of bcc-(Fe, Co[Si]) and fccCo phases for COF samples and bcc-(Fe, Ni[Si]) for NIF ones [7]. The thermal treatments on the as-cast ribbons were carried out in air by Joule-heating during short time (always below 5 min).…”
Section: Sample Treatmentsmentioning
confidence: 99%
“…The average size of the crystallites ͑D͒ was evaluated from Scherrer's formula using the Gaussian function deducted from the fitting. 12,13 The coercive field of the samples was evaluated from the hysteresis loops obtained by a fluxmetric method in the range of 20-300 Hz. The extrapolation to zero frequency allowed deducing the coercivity representative of the bulk in quasistatic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The substitution of Fe atoms by additional elements in Finemet alloys, such as Co, Al or Cr, have been investigated extensively [2][3][4][5][6]. Recently, the research concerning a series of Ni x Fe 73.5 À x Si 13.5 Nb 3 B 9 Cu (0rx r25) alloys reported by Agudo et al and Elbaile et al, has opened a new field on the optimization of the soft magnetic properties [7,8], and the alloy with x¼5 shows the best soft magnetic characteristic [9]. However, the Curie temperature of amorphous phase (T am c ) for Ni 5 Fe 68.5-Si 13.5 Nb 3 B 9 Cu alloy is lower, just about 333 1C [7], which limits its application at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%